Optimal Singular Value Decomposition Based Big Data Compression Approach in Smart Grids - Hashemipour, Naser; Aghaei, Jamshid; Kavousi-fard, Abdollah; Niknam, Taher; Salimi, Ladan; del Granado, Pedro Crespo; Shafie-Khah, Miadreza; Wang, Fei; Catalão, João P. S. (IEEE, 2021)
The smart grid is a fully automatic delivery grid for electricity power with a two-way reliable flow of electricity and information among different equipment on the grid. Smart meters and sensors monitoring the system provide a huge amount of data in various part of smart grid. To logically manage this trouble, a new lossy data compression approach for big data compression is proposed. The optimal singular value decomposition (SVD) is applied to a matrix that achieves the optimal number of singular values to the sending process, and the other ones will be neglected. This goal is done due to the quality of retrieved data and the compression ratio. In the presented scheme, to implement the optimization framework, various intelligent optimization methods are used to determine the number of optimal values in the elimination stage. The efficiency and capabilities of the proposed method are examined using a wide range of data types, from electricity market data to image processing benchmarks. The comparisons show that the compression level obtained by the proposed method can dominate the points given by the existing SVD rank reduction methods. Also, as the other finding of this article, the performance of the rank reduction methods depends on the application and data types. It means that a rank reduction method can reveal a good performance in one application and performs unacceptably for another purpose. So, the optimized rank reduction can pave the way toward a robust and reliable performance.
Keywords: singular value decomposition (SVD); smart grids; data compression; big data; optimisation; fi=Sähkötekniikka|en=Electrical Engineering|